Characterization of the complete chloroplast genome of Engelhardia roxburghiana (Juglandaceae). Issue 1 (2nd January 2020) - Ling, Li-Zhen; Zhang, Shu-Dong
Abstract: Engelhardia roxburghiana is a traditional Chinese medicine in the Juglandaceae family. In this study, the complete chloroplast (cp) genome sequence of E. roxburghiana was reported and characterized. The cp genome is 161, 550 bp in length and contains a pair of inverted repeats (IRs, 25, 862 bp) separated by a large (90, 937 bp) and small (18, 889 bp) single-copy regions. A total of 113 unique genes were predicted, including 79 protein-coding genes, 30 tRNA genes and 4 rRNA genes. The phylogenetic analysis suggested that E. roxburghiana is resolved as a sister group to the clade of subfam. Juglandoideae.